Compositions, their preparation and their use
By using a composition of adhesive and metal inorganic salt clusters in the surface coating, the problem that existing coatings are difficult to have multiple excellent properties at the same time is solved, and the overall performance improvement of the coating is achieved.
Patent Information
- Application Number
- CN202380038320.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-05
- Filing Date
- 2023-05-02
- Publication Date
- 2025-04-25
AI Technical Summary
It is difficult for existing surface coatings to have high hardness, modulus, wear resistance, scratch resistance and chemical resistance at the same time.
Using a composition comprising at least one binder and at least one metal inorganic salt cluster, a coating with excellent mechanical and chemical properties is formed by mixing the binder with the metal inorganic salt cluster.
The coating has achieved significant improvements in hardness, modulus, wear resistance, scratch resistance and chemical resistance, and meets multiple performance requirements.
Smart Images

Figure BDA0005117207690000111 
Figure BDA0005117207690000112
Abstract
Description
Technical Field
[0001] The present invention relates to a composition containing a binder and a metal inorganic salt cluster, its preparation, and its use for coating, more particularly its use for surface coating (including but not limited to floor coating). Background Art
[0002] Hardness is one of the most important properties of many types of coatings, especially surface coatings, including but not limited to floor coatings, industrial coatings, and wood coatings. In order to obtain excellent hardness, 2K systems with isocyanate crosslinking are usually used in surface coatings. However, 1K systems are always more attractive due to their ease of application. In addition to hardness, it is also desirable to have good properties regarding modulus, wear resistance, scratch resistance, and chemical resistance of the surface coating.
[0003] Therefore, there is a need for a surface coating having good performance in at least one of the properties of hardness, modulus, wear resistance, scratch resistance and chemical resistance; preferably having good performance in hardness and modulus, wear resistance, scratch resistance and chemical resistance. Summary of the invention
[0004] An object of the present disclosure is to provide a composition comprising at least one binder and at least one metal inorganic salt cluster, wherein the at least one metal inorganic salt cluster is composed of M a X b It represents, wherein M is a metal cation, X is an inorganic anion, and a and b are each independently an integer of 1 to 3.
[0005] Another object of the present disclosure is to provide a method for preparing the composition of the present disclosure.
[0006] A third object of the present disclosure is to provide use of the composition in coating, preferably surface coating. DETAILED DESCRIPTION
[0007] Unless otherwise defined, all terms / terminology / nomenclature used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0008] The expressions "a," "an," and "the" when used to qualify a term include both the plural and singular forms of the term.
[0009] As used herein, the term "polymer" or "polymers" includes both one or more homopolymers (i.e., polymers prepared from a single reactive compound) and one or more copolymers (i.e., polymers prepared by the reaction of at least two polymer-forming reactive monomer compounds).
[0010] The term "salt" means a chemical compound consisting of an ionic assembly of cations and anions.
[0011] The name (meth)acrylate and similar names are used herein as a shorthand notation for "acrylate and / or methacrylate".
[0012] Unless otherwise indicated, all percentages and ratios are expressed by weight.
[0013] An object of the present disclosure is to provide a composition comprising at least one binder and at least one metal inorganic salt cluster, wherein the at least one metal inorganic salt cluster is composed of M a X b It represents, wherein M is a metal cation, X is an inorganic anion, and a and b are each independently an integer of 1 to 3.
[0014] It was unexpectedly discovered that when a composition comprises at least one binder of the present disclosure and at least one metal inorganic salt cluster, the resulting composition exhibits good hardness and at least one of the properties of modulus, abrasion resistance, scratch resistance, and chemical resistance.
[0015] As used herein, the term "adhesive" refers to an organic polymer compound responsible for forming a film in addition to other components of the coating composition. The coating composition may include at least one adhesive. The adhesive may be present in an amount of 1 to 90wt.%, more preferably 20 to 80wt.%, most preferably 50 to 70wt.% based on the gross weight of the coating composition. In particular, for surface coatings, including but not limited to floor coatings, wall coatings and wall coatings and coatings for windows and doors, the adhesive may be present in an amount of 1 to 80wt.%, or 3 to 50wt.% based on the gross weight of the coating composition.
[0016] There are no particular restrictions on the binders that may be present in the present disclosure. Binders that can be used in the composition include, but are not limited to, alkyd resins, epoxy resins, polyurethanes, vinyl acetate / ethylene copolymers, waterglass, more particularly potassium waterglass, and also binders based on (meth)acrylates, styrenes and / or vinyl esters such as styrene acrylate or butyl acrylate.
[0017] For example, in one embodiment, the adhesive comprises a polymer and / or copolymer of vinyl acetate, ethylene, styrene, (meth)acrylate, butyl acrylate, or a mixture of these polymers and / or copolymers. In another embodiment, the adhesive comprises polyurethane, (meth)acrylate, alkyd resin, epoxy resin, and any mixture thereof. In a preferred embodiment, the adhesive comprises (meth)acrylate, polyurethane, or any mixture thereof.
[0018] In another embodiment, the solid content of the adhesive in the present disclosure is 20% to 65%, preferably 25% to 60%, more preferably 30% to 50%.
[0019] In one embodiment, the metal cation M in the metal inorganic salt cluster is a monovalent, divalent or trivalent metal cation. Examples of such metal cations include, but are not limited to, Na + , K + 、Be 2+ , Ca 2+ Mg 2+ , Sr 2+ , Ba 2+ and Al 3+ In a preferred embodiment, the metal cation M is a divalent metal. Examples of such metal cations include, but are not limited to, Ca 2+ Mg 2+ , Sr 2+ and Ba 2+ More preferably, the metal cation M is Ca 2+ Mg 2+ and Ba 2+ ; Most preferably Ca 2+ .
[0020] In another embodiment, the anion X in the metal inorganic salt cluster is a divalent or trivalent anion. Examples of such anions include, but are not limited to, CO3 2- and PO4 3- , preferably the anion X is PO4 3- .
[0021] In one embodiment, the particle size of the metal inorganic salt cluster is 0.4 to 9nm or 0.4 to 7nm, preferably 0.4 to 5nm or 0.6 to 5nm, more preferably 0.4 to 3nm or 0.6 to 2nm, most preferably 0.6 to 1.5nm or 0.8 to 1.2nm. The particle size of the metal inorganic salt is measured by transmission electron microscopy (TEM, HT-7700, Hitachi (Hitachi), Japan). The particle size of the metal inorganic salt of the present disclosure is calculated by the average particle size of the particle sizes of 100 particles obtained from the TEM image.
[0022] In another embodiment, the metal inorganic salt clusters are present in an amount of 0.1 to 10 wt.%, preferably 0.3 to 8 wt.%, more preferably 0.5 to 5 wt.%, most preferably 1 to 3 wt.%, based on the weight of the composition.
[0023] The metal inorganic salt clusters are prepared according to the method disclosed in CN 110157132 B. For example, the metal inorganic salt clusters of Ca3(PO4)2 can be prepared by the following method: triethylamine as a stabilizer, CaCl2·2H2O as a Ca source, and H3PO4 as a phosphorus source are added to an organic solvent to produce the metal inorganic salt clusters of Ca3(PO4)2, wherein the reaction temperature is about 25° C. The organic solvent can be any commonly used organic solvent, and examples of such organic solvents are ethanol, ethylene glycol and glycerol or mixtures thereof.
[0024] In another embodiment, the solids content of the composition of the present disclosure is 10% to 80%, preferably 20% to 65%, more preferably 25% to 60%, most preferably 25% to 50%.
[0025] Another object of the present disclosure is to provide a method for preparing the composition of the present invention.
[0026] In one embodiment, the composition is prepared by mixing at least one binder and at least one metal inorganic cluster at room temperature; optionally adding other components of at least one of a pigment, a filler, a solvent, a preservative, a thickener, a dispersant, and a defoamer under stirring.
[0027] The third object of the present disclosure is to provide use of such a composition in surface coating.
[0028] In addition, the surface coating composition may contain further components, such as pigments, fillers, solvents, water, and further additives such as preservatives, thickeners, dispersants and defoamers.
[0029] Suitable pigments include, for example, inorganic white pigments, such as titanium dioxide, barium sulfate, zinc oxide, zinc sulfide, basic lead carbonate, antimony trioxide and lithopone; inorganic colored pigments, such as iron oxides, carbon black, graphite, zinc yellow, zinc green, ultramarine, manganese black, antimony black and manganese violet; organic colored pigments, such as indigo, azo dyes, anthraquinoid and indidental dyes, and dioxazines, quinacridones, phthalocyanines, isoindolinones and metal complex pigments. Also suitable are synthetic white pigments with air inclusions to increase light scattering, such as The pigment, if present, may be present in an amount of 20 to 80 wt.%, preferably 50 to 75 wt.%, in the case of wall paints, or in an amount of not more than 25 wt.%, preferably not more than 15 wt.%, most preferably not more than 10 wt.%, in the case of transparent or translucent coatings, based on the total weight of the coating composition.
[0030] Suitable fillers include, for example, kaolin, talc, mica, magnesite, alkaline earth carbonates such as calcite or chalk, magnesium carbonate, dolomite, alkaline earth sulfates such as calcium sulfate, silicon compounds such as silicon dioxide or aluminum silicate or magnesium aluminum silicate, and aluminum oxide or aluminum oxide hydrate. Fillers, if present, may be present in an amount of 1 to 90 wt.%, preferably 20 to 60 wt.%, in the case of wall paints, or in an amount of not more than 5 wt.%, preferably not more than 2 wt.%, most preferably not more than 1 wt.%, based on the total weight of the coating composition.
[0031] Suitable organic solvents include, for example, trimethylpentane, propylene glycol or dipropylene glycol butyl ether.The organic solvent, if present, may be present in an amount of less than 5 wt. %, based on the total weight of the coating composition.
[0032] Suitable preservatives include, for example, isothiazolinone formulations, such as 2-methyl-2H-isothiazol-3-one or 1,2-benzisothiazolin-3H-one. The preservative may be present in an amount of less than 2 wt.%, preferably less than 0.3 wt.%, based on the total weight of the coating composition.
[0033] Suitable thickeners include, for example, cellulose ethers, bentonites, polysaccharides, fumed silica, phyllosilicates, or polyurethane thickeners.The thickener may be present in an amount of less than 1 wt.%, preferably less than 0.6 wt.%, based on the total weight of the coating composition.
[0034] Suitable dispersants include, for example, alkylbenzene sulfonates, polycarboxylates, fatty acid amines, or salts of polyacrylic acid.The dispersant may be present in an amount of less than 2 wt.%, preferably 0.001 to 0.5 wt.%, based on the total weight of the coating composition.
[0035] Suitable defoamers include, for example, poly(organo)siloxanes, silicone oils or mineral oils.The defoamer may be present in an amount of less than 1 wt.%, more preferably 0 to 0.5 wt.%, based on the total weight of the coating composition.
[0036] The present invention is further shown and illustrated in the following examples, however the present invention is not limited to the embodiments described in the examples.
[0037] Examples
[0038] The following materials were used in the preparation of the compositions and in the testing of the compositions.
[0039] In the following description, parts and percentage values are by wt. % unless otherwise indicated.
[0040] Calcium chloride dihydrate (CaCl2·2H2O, 99.0%) from Sigma-Aldrich (USA)
[0041] Phosphoric acid (≥85%) from Sinopharm Chemical Reagent Co., Ltd.
[0042] Triethylamine (TEA, (C2H5)3N; 99%) was from Sinopharm Chemical Reagent Co., Ltd.
[0043] Ethanol (C2H5OH, 99.7%) was from China National Pharmaceutical Group Chemical Reagent Co., Ltd.
[0044] HAP: Hydroxyapatite nanoparticles from Aladdin's Reagent Co., Ltd., China
[0045] BDG: Ethylene glycol dibutyl ether from China National Pharmaceutical Group Chemical Reagent Co., Ltd.
[0046] AMP 95: from Dow Chemical
[0047] Anticide MBS: From Thor
[0048] Dispex CX 4320: from BASF
[0049] Foamstar SI 2210: from BASF
[0050] Clariant Colanyl Black N131-CN from Clariant
[0051] Kronos 2310 powder: from Dupont
[0052] Omyacarb 2 powder: from Omya
[0053] Omyacarb 5 powder: from Omya Corporation
[0054] 800 mesh talc powder: from Shandong Jinqi Minerals Co., Ltd.
[0055] DPND: Dipropylene glycol butyl ether from China National Pharmaceutical Group Chemical Reagent Co., Ltd.
[0056] Texonal: From Eastman
[0057] Rhevious PU 1331: from BASF
[0058] Binder A: Acronal EDGE 6283 from BASF, an acrylic dispersion with butyl acrylate, styrene and acrylic acid as monomers, 42.1% solids content
[0059] Binder B: HPUD 1591 from Siwochem, polyurethane dispersion with isophorone diisocyanate, polycarbonate and dimethylolpropionic acid, solids content 36%
[0060] Preparation of CPO
[0061] 5.88 g of CaCl2·2H2O was dissolved in 0.8 L of ethanol. Then, 110.9 mL of TEA was added to the above solution under magnetic stirring at room temperature for 30 min. Then, H3PO4 alcohol solution (2.09 mL of H3PO4 dissolved in 40 mL of ethanol) was added to the above solution under magnetic stirring at room temperature overnight. The gel was obtained by centrifugation at 8000 rpm and washing with ethanol several times. CPO with a solid content of 5% was obtained. The size of the prepared CPO was 0.98 nm.
[0062] Example 1
[0063] First, 72.68g of Adhesive A was uniformly mixed with 30.5g of CPO obtained from the above process to form a homogeneous emulsion. 6g of BDG was added to the above emulsion and mixed for 2 minutes under stirring; 2g of AMP 95 was slowly added and mixed until a homogeneous emulsion was obtained under stirring. After blending for 2 minutes, 0.4g of Antiicide MBS and 1.32g of water were added and mixed for 1 minute under stirring. 4.12g of Dispex CX 4320 was added and mixed for 2 minutes under stirring, 0.6g of Foamstar SI 2210 was added and mixed for 2 minutes under stirring, and 1.2g of Clariant Colanyl BlackN131-CN was added and mixed for 2 minutes under stirring. Then add 16g of Kronos 2310 powder, 8g of Omyacarb 2 powder, 9g of Omyacarb5 powder and 3.4g of 800 mesh talcum powder under stirring, and mix until the mixture is dispersed. After blending at high speed (that is, 900rpm) for 20 minutes to obtain 5.5 or greater Hegman grind, under stirring, another homogeneous emulsion of 72.68g of adhesive A and 30.5g of CPO obtained from the above process is added, and mixed for 2 minutes. Finally, 0.6g of Foamstar SI 2210 is added again under stirring.
[0064] Example 2
[0065] First, 85g of adhesive B was uniformly mixed with 71.4g of CPO obtained from the above process to form a homogeneous emulsion. 3g of DPND and 2g of Texonal were added to the above emulsion and mixed for 2 minutes under stirring; 2g of AMP95 was slowly added and mixed until a homogeneous emulsion was obtained under stirring. After blending for 2 minutes, 0.4g of Antiicide MBS was added and mixed for 1 minute under stirring. 4.12g of Dispex CX 4320 was added and mixed for 2 minutes under stirring, and 0.6g of Foamstar SI 2210 was added and mixed for 2 minutes under stirring. 1.2g of Clariant Colanyl Black N131-CN was added and mixed for 2 minutes under stirring. Then 16g of Kronos 2310 powder, 8g of Omyacarb 2 powder, 9g of Omyacarb5 powder and 3.4g of 800 mesh talc powder were added under stirring and mixed until the mixture was dispersed. After blending at high speed (i.e., 900 rpm) for 20 minutes to obtain a Hegman grind fineness of 5.5 or greater, 85 g of Binder B and 71.4 g of another homogenous emulsion of CPO obtained from the above process were added under stirring and mixed for 2 minutes. Finally, 0.6 g of Foamstar SI 2210 was added again under stirring.
[0066] Comparative Example 1
[0067] First, 72.68g of adhesive A was added under stirring, and 6g of BDG was further added and mixed for 2 minutes under stirring; 2g of AMP 95 was slowly added and mixed under stirring until a homogeneous emulsion was obtained. After blending for 2 minutes, 0.4g of Antiicide MBS and 1.32g of water were added and mixed for 1 minute under stirring. 4.12g of DispexCX 4320 was added and mixed for 2 minutes under stirring, 0.6g of Foamstar SI 2210 was added and mixed for 2 minutes under stirring, 0.6g of Rheovis PU 1331 was slowly added under stirring to adjust the viscosity and mixed for 5 minutes, and 1.2g of Clariant Colanyl Black N131-CN was added and mixed for 2 minutes under stirring. Then add 16g of Kronos 2310 powder, 8g of Omyacarb 2 powder, 9g of Omyacarb 5 powder and 3.4g of 800 mesh talcum powder under stirring, and mix until the mixture is dispersed. After blending at high speed (that is, 900rpm) for 20 minutes to obtain 5.5 or greater Hegman grinding fineness, under stirring, another homogeneous emulsion of 72.68g of adhesive A is added, and mixed for 2 minutes. Finally, under stirring, 0.6g of Foamstar SI 2210 is added again.
[0068] Comparative Example 2
[0069] First, 72.68g of adhesive A was uniformly mixed with 1.525g of HAP to form a homogeneous emulsion, and 6g of BDG was further added and mixed for 2 minutes under stirring; 2g of AMP 95 was slowly added and mixed under stirring until a homogeneous emulsion was obtained. After blending for 2 minutes, 0.4g of Antiicide MBS and 1.32g of water were added and mixed for 1 minute under stirring. 4.12g of Dispex CX 4320 was added and mixed for 2 minutes under stirring, 0.6g of Foamstar SI2210 was added and mixed for 2 minutes under stirring, 0.6g of Rheovis PU 1331 was slowly added to adjust the viscosity and mixed for 5 minutes under stirring, and 1.2g of Clariant Colanyl Black N131-CN was added and mixed for 2 minutes under stirring. Then under agitation add 16g of Kronos 2310 powder, 8g of Omyacarb 2 powder, 9g of Omyacarb 5 powder and 3.4g of 800 mesh talcum powders, and mix until the mixture is dispersed. After blending at a high speed (that is, 900rpm) for 20 minutes to obtain 5.5 or larger Hegman grinding fineness, under agitation another homogeneous emulsion of 72.68g of adhesive A and 1.525g of HAP is added, and mixed for 2 minutes. Under agitation again 0.6g of Foamstar SI 2210 is added. Finally, under agitation slowly add 0.6g of Rheovis PU 1331 to regulate viscosity and mix for 5 minutes.
[0070] Comparative Example 3
[0071] First, 85 g of adhesive B was added under stirring, 3 g of DPND and 2 g of Texonal were added to the above emulsion under stirring and mixed for 2 minutes; 2 g of AMP 95 was slowly added and mixed under stirring until a homogeneous emulsion was obtained. After blending for 2 minutes, 0.4 g of Antiicide MBS was added and mixed for 1 minute under stirring. 4.12 g of Dispex CX 4320 was added under stirring and mixed for 2 minutes, 0.6 g of Foamstar SI 2210 was added under stirring and mixed for 2 minutes, 2 g of Rheovis PU 1331 was slowly added under stirring to adjust the viscosity and mixed for 5 minutes, and 1.2 g of Clariant Colanyl Black N131-CN was added under stirring and mixed for 2 minutes. The talcum powder of Kronos 2310 of 16g, Omyacarb 2 powder of 8g, Omyacarb 5 powder of 9g and 3.4g are added under agitation then, and mix until the mixture is dispersed. After blending 20 minutes at a high speed (that is, 900rpm) to obtain 5.5 or larger Hegman grinding fineness, under agitation another homogeneous emulsion of adhesive B of 85g is added, and mixed 2 minutes. Under agitation again the Foamstar SI 2210 of 0.6g is added. Finally, under agitation slowly add the Rheovis PU 1331 of 2g to regulate viscosity and mix 5 minutes.
[0072] Comparative Example 4
[0073] First, 85g of adhesive B was uniformly mixed with 3.57g of HAP to form a homogeneous emulsion, 3g of DPND and 2g of Texonal were added to the above emulsion under stirring and mixed for 2 minutes; 2g of AMP 95 was slowly added and mixed under stirring until a homogeneous emulsion was obtained. After blending for 2 minutes, 0.4g of Antiicide MBS was added and mixed for 1 minute under stirring. 4.12g of Dispex CX 4320 was added and mixed for 2 minutes under stirring, 0.6g of Foamstar SI2210 was added and mixed for 2 minutes under stirring, 2.6g of Rheovis PU 1331 was slowly added under stirring to adjust the viscosity and mixed for 5 minutes, and 1.2g of Clariant Colanyl Black N131-CN was added and mixed for 2 minutes under stirring. Then under agitation, add 16g of Kronos2310 powder, 8g of Omyacarb 2 powder, 9g of Omyacarb 5 powder and 3.4g of 800 mesh talcum powder, and mix until the mixture is dispersed. After blending at high speed (that is, 900rpm) for 20 minutes to obtain 5.5 or larger Hegman grinding fineness, under agitation, another homogeneous emulsion of 85g of adhesive B and 3.57g of HAP is added, and mixed for 2 minutes. Under agitation, 0.6g of Foamstar SI 2210 is added again. Finally, under agitation, slowly add 2.6g of RheovisPU 1331 to adjust viscosity and mix for 5 minutes.
[0074] Each example and comparison example was tested as follows:
[0075] For the pencil hardness test, the composition was applied to a non-asbestos fiber cement board using a manual film applicator and the thickness of the scratch coating was 150 μm. The intermediate drying time between the first and second coatings was 24 h. After application of the last composition, the sample was dried for 1 week at 23° C. and 50% relative humidity. The test instrument and operating procedure were pre-determined according to GB / T6739-2006.
[0076] For the wear resistance test, the type of rubber grinding wheel selected was CS-17, and the load of each rubber grinding wheel was 750 g. All compositions were pre-ground for 100 turns, and the weight was set to w1. After grinding for 500 turns, the weight of the sample was set to w2. The difference between w1 and w2 reflects the wear resistance capability.
[0077] For the chemical resistance test, the sample preparation process is the same as the hardness test. Several drops of liquid, including water, oil, 10% H2SO4 solution, and 20% NaOH solution, are added to the test plate. For each liquid, the test time is 168h, 72h, 48h, and 72h, respectively. After the test, the test area is washed with water and the sample is checked for discoloration.
[0078] Nanoindentation modulus tests were performed using an Agilent G200 nanoindenter equipped with a continuous stiffness measurement module (modulem), and the average value was calculated based on five tests.
[0079] Micro scratch tests were performed using a micro scratch tester (UNHT / MCT / MST, Anton Paar GmbH, Austria). All scratch test samples were scratched at a constant normal load of 100 mN at a speed of 200 μm min -1 The test was performed at a speed of . For each sample, five scratches were made in each test area. The scratch distance was 500 μm, and each scratch was at least 50 μm away from the next scratch. The average scratch contact depth value at different distances for each scratch was calculated. Finally, the average value was calculated again based on the five scratches.
[0080] The results of pencil hardness, abrasion resistance, nanoindentation modulus, and average scratch contact depth of each example and comparative example are shown in Table 1 below.
[0081] Table 1
[0082]
[0083] The results of the chemical resistance test of each Example and Comparative Example are shown in Table 2 below.
[0084] Table 2
[0085]
[0086] In order to more accurately compare the chemical resistance of each example and the comparative example, for samples with slight discoloration, '+' is used to distinguish the discoloration degree of the sample. More '+' means more obvious discoloration.
Claims
1. A composition comprising: 1) at least one adhesive, and 2) At least one of M a X b The metal-inorganic cluster represented by ; wherein M represents a monovalent, divalent or trivalent metal cation; X represents a divalent or trivalent inorganic anion; and a and b are each independently an integer of 1 to 3.
2. The composition according to claim 1, wherein M is selected from the group consisting of: Na + , K + 、Be 2+ , Ca 2+ Mg 2+ , Sr 2+ , Ba 2+ and Al 3+ Preferably M is selected from the group consisting of: Ca 2+ Mg 2+ , Sr 2+ and Ba 2+ More preferably, M is selected from the group consisting of: Ca 2+ Mg 2+ , and Ba 2+ ; Most preferably M is Ca 2+ .
3. The composition according to claim 1 or 2, wherein X is CO3 2- PO4 3- or a mixture thereof, preferably X is PO4 3- .
4. The composition according to any one of claims 1 to 3, wherein The particle size of the at least one metal inorganic cluster is from 0.4 to 9 nm, preferably from 0.4 to 5 nm, more preferably from 0.4 to 3 nm, most preferably from 0.6 to 1.5 nm, even more preferably or from 0.8 to 1.2 nm.
5. The composition according to any one of claims 1 to 4, wherein The at least one metal inorganic cluster is present in an amount of 0.1 to 10 wt.%, preferably 0.3 to 8 wt.%, more preferably 0.5 to 5 wt.%, most preferably 1 to 3 wt.%, based on the total weight of the composition.
6. The composition according to any one of claims 1 to 5, wherein The binder is present in an amount of 1 to 90 wt.%, more preferably 20 to 80 wt.%, most preferably 50 to 70 wt.%, based on the total weight of the composition.
7. The composition according to any one of claims 1 to 6, wherein The solids content of the composition is from 10% to 80%, preferably from 20% to 65%, more preferably from 25% to 60%, most preferably from 25% to 50%.
8. The composition according to any one of claims 1 to 7, wherein The composition further comprises at least one of a pigment, a filler, a solvent, a preservative, a thickener, a dispersant and a defoaming agent.
9. A method for preparing a composition according to any one of claims 1 to 8, wherein At least one binder and at least one metal inorganic cluster are mixed at room temperature; further components of at least one of a pigment, a filler, a solvent, a preservative, a thickener, a dispersant and a defoamer are optionally added under stirring.
10. Use of the composition according to any one of claims 1 to 8 for coating a surface, preferably a floor.
Citation Information
Patent Citations
A high-strength organic-inorganic homogeneous composite material, its preparation method, and its application.
CN110157132B